Avatars de Napalm Girl, June 8, 1972 (Nick Ut) : variations autour d’une icône de la Guerre du Vietnam - Anne LESME (E-REA)
This essay examines and analyses the iconic status of Nick Ut’s Vietnam photograph Napalm Girl (“Vietnam Napalm”, 1972) and its recycling in postmodern art and various media. Since it was published, this image has stood for the trauma of the Vietnam War and its lasting effects on the American collective memory. The symbolic crucifixion of the naked child is all the more powerful as the spectator, in this decisive moment, is facing horror and is invited to act. From the moment the picture reappeared in the mid-1980s, a compulsive repetition occurred through various artistic media. While the The damages caused by the United States and represented by the child victim remain constant, the initial anti-war message has been transformed into an anti-imperialistic one, closely related to the American consumer society. As such, the avatars of the Napalm Girl ultimately invite the spectator to conduct a critical reflection in visual media about the idolatrous behaviors elicited by icons.